Protocolos administrativos y su incidencia en el clima laboral de las Secretarias del Municipio de Jujan - Icaza Mendoza, Paola Beatriz (2022)
The following case study entitled "ADMINISTRATIVE PROTOCOLS AND ITS IMPACT ON THE WORK ENVIRONMENT OF THE SECRETARIATS OF THE MUNICIPALITY OF JUJAN", aims to demonstrate and demonstrate the importance of administrative protocols within the different departments of an organization, be they public or private. . At the same time, it will focus on compiling all the information on how essential administrative protocols are in the secretaries of the municipality of Jujan, in turn, it will be chosen to interview a group of them, to know what their criteria are in relation to the subject. . The bosses or personnel who hold managerial or superior positions will be investigated, since they are responsible for fully complying with the rules in the company and thus in said company there is excellent management of administrative protocols that facilitate a good working environment, because although it is true where a good administrative protocol flows, there is an excellent work environment in the different employees. Considering the above, all this will benefit not only a favorable work environment, but also help the administrative attention to customers or different citizens who benefit from this service to be satisfactorily attended without their requirements not being met. or solved correctly. This will mean that the citizens benefiting from the work of the municipality of the Jujan canton, feel satisfied and pleased, that will generate that this municipality gain good prestige and that the company has considerable growth.